Efficacy and adverse effects of peripheral nerve blocks and local infiltration anesthesia after arthroscopic shoulder surgery: A Bayesian network meta-analysis - Liu, Zheng; Li, Yi-bo; Wang, Ji-hua; Wu, Guang-han; Shi, Peng-cai (Frontiers in Medicine, 2022)
Study objective: This network meta-analysis aims to quantitatively assess and compare the efficacy and safety of the regional analgesia techniques for arthroscopic shoulder surgery (ASS) in randomized controlled trials (RCTs). Design: A network meta-analysis was performed for all direct and indirect comparisons based on the Bayesian framework to select the best modality, including six interventions and 36 RCTs. Setting: Post anesthesia care unit (PACU) and ward. Patients: Thirty-six randomized controlled trials involving 3124 patients (ASA I-III) were included in the final analysis. Interventions: Six interventions involving five nerve blocks and one local analgesia (LIA): interscalene nerve block (ISB), continuous interscalene nerve block (CISB), supraclavicular nerve block (SCB), suprascapular nerve block (SSNB), suprascapular nerve block and axillary nerve block (SSAX), and local infiltration analgesia (LIA) combined with general anesthesia undergoing arthroscopic shoulder surgery were included in the network meta-analysis. Measurements: The primary outcome was pain scores (VAS or NRS); the secondary outcomes were opioid consumption and the incidence of adverse events. Main results: For pain scores and reducing postoperative opioid consumption, interscalene nerve block (ISB) provided the best analgesic effects after surgery. However, suprascapular nerve block and axillary nerve block (SSAX), suprascapular nerve block (SSNB) significantly reduced the incidence of compilations compared to ISB group. Conclusions: Although several analgesic techniques (SSNB, SNNB+ANB, SCB, LIA) were the potential alternative to ISB and CISB to provide effective anesthesia for ASS with fewer complications, none of the other analgesic techniques discussed has been consistently shown to be superior or effective to ISB in the early postoperative period. Keywords: Arthroscopic shoulder surgery, Pain management, Nerve block, Complications, Bayesian network meta-analysis.